The role of prothrombrin complex concentrate in the management of trauma-induced coagulopathy: an integrative review (Research, Society and Development, 2023)
Introduction: Trauma is a disease that kills almost 6 million people every year. The bleeding resulting from trauma triggers a complex coagulopathy, which requires immediate treatment to improve patient survival. Treatment is based on removing the source of bleeding, using blood products and coagulation factor concentrates, associated with permissive hypotension and controlled replacement of crystalloid fluids. Objective: To evaluate the effects of using prothrombin complex concentrates in the management of trauma-induced coagulopathy in the emergency department. Methodology: this study is an integrative literature review. The search mechanism used within the databases was: (Bleeding OR Hemorrhage OR Hemostasis OR “Blood Coagulation Disorders") AND (“Prothrombin Complex Concentrates”). Were included articles from 2017 to 2022, full texts available in English, Portuguese and Spanish. Letters, editorials and case reports, that did not correspond to the theme and duplicates were excluded. Results: After applying the inclusion and exclusion criteria, 37 articles were selected for full reading, resulting in a final sample of 15 articles to compose this integrative review, nine from MEDLINE, five from SCOPUS and one from SCIENCEDirect. Conclusion: The prothrombin complex concentrate is an important adjuvant in the management of trauma-induced coagulopathy, due to its ability to reduce the international normalized ratio and mortality without increasing the risk of thromboembolic events.